1997
DOI: 10.1111/j.1600-0536.1997.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on sodium lauryl sulfate (SLS) exposure tests

Abstract: This report reviews the clinical and histopathological reactions caused by sodium lauryl sulfate (SLS), and the non-invasive methods that can characterize these reactions. Furthermore, SLS exposure techniques and factors that may influence the outcome of these exposures are discussed. Finally, guidelines are introduced for each exposure technique in order to have a uniform approach to SLS testing in man. Since different study aims warrant different testing conditions, we have proposed 2 categories, namely susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(98 citation statements)
references
References 108 publications
3
92
0
3
Order By: Relevance
“…Specifying exact and small skin areas for repeated measurements within clinical research is therefore necessary [11,12,13,15]. Furthermore, several skin parameters are usually obtained to achieve a comprehensive picture of the skin barrier function and possible treatment effects [6,9,16,17]. It is known that even slight manipulations like placing a probe or a camera head on the skin surface influence the skin function (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specifying exact and small skin areas for repeated measurements within clinical research is therefore necessary [11,12,13,15]. Furthermore, several skin parameters are usually obtained to achieve a comprehensive picture of the skin barrier function and possible treatment effects [6,9,16,17]. It is known that even slight manipulations like placing a probe or a camera head on the skin surface influence the skin function (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A 2% concentration of SLS in distilled water (high purity 99% from Henkel KOGA, Düsseldorf, Germany) was used according to recently published guidelines [13]. This concentration was chosen because previous tests had shown that the irritant produced a response possible to judge by a visual score.…”
Section: Methodsmentioning
confidence: 99%
“…Tupker et al [106] studied the detergent sodium lauryl sulfate, normally used to induce contact irritant dermatitis, which induced dose-related stinging pain, vasodilatation and pronounced prostaglandin E2 release after infusion. In a study of UV-B-irradiated skin, infusion of both bradykinin B1 and B2 agonists enhanced the pain sensation and axon reflex vasodilatation.…”
Section: Retrodialysis In Experimental Human Studiesmentioning
confidence: 99%